Apnoeic oxygenation in pediatric anesthesia: better safe than sorry! - Uzun, Davut D.; Hezel, Felix; Mohr, Stefan; Weigand, Markus A.; Schmitt, Felix (BMC anesthesiology, 2025)
Children, especially neonates and infants, are at particularly high risk of hypoxemia during induction of anesthesia. The addition of nasal apnoeic oxygenation (ApOx) during tracheal intubation should prolong safe apnoea time without desaturation and reduce the risk of hypoxemia. Despite the recommendations in the relevant European guidelines, their implementation in pediatric anesthesia in Germany is not yet known. A survey was conducted in July and October 2024 via email to all registered members of the scientific working group on airway management, the scientific working group on pediatric anesthesia of the German Society of Anesthesiology and Intensive Care Medicine (DGAI) and hospitals of all levels in Germany. Participants were asked about their personal and institutional background and the use of ApOx in pediatric anesthesia in their institution. Of the eight hundred participants invited, 304 anesthetists completed the survey (response rate 38%). In addition, 36 of 109 invited anesthetists from the scientific working group on pediatric anesthesia were interviewed as a separate expert group. 201 (66.1%) of the anesthetists surveyed in the general group stated that they worked regular in pediatric anesthesia (pediatric anesthesia expert group: 94.4%). 64.2% of the general respondents considered pediatric patients to be at an increased risk of reduced apnoea time. 46.7% of the general participants are of the opinion that pediatric patients should generally not receive ApOx during induction of anesthesia. If ApOx is performed, then most likely with a standard nasal cannula. ApOx was generally used in infants with an oxygen flow rate of ≤ 2 l/min or 0.2 l/kg bodyweight/min. A relevant proportion of anesthetists were unaware that current European guidelines recommend ApOx for neonates and infants (general participants: 62.5%, pediatric anesthesia expert group: 39%). Despite the recommendations in the guidelines, the use of ApOx does not appear to be standard practice at present. Furthermore, the surveyed physicians exhibited considerable uncertainty regarding ApOx. It is imperative that further improvements are made in the dissemination of the current guidelines with a view to enhancing patient safety during pediatric anesthesia.